2016
DOI: 10.1090/proc/13170
|View full text |Cite
|
Sign up to set email alerts
|

Equidistribution of expanding curves in homogeneous spaces and Diophantine approximation on square matrices

Abstract: Abstract. In this article, we study an analytic curve ϕ : I = [a, b] → M(n × n, R) in the space of n by n real matrices, and show that if ϕ satisfies certain geometric conditions, then for almost every point on the curve, the Diophantine approximation given by Dirichlet's Theorem is not improvable. To do this, we embed the curve into some homogeneous space G/Γ, and prove that under the action of some expanding diagonal flow A = {a(t) : t ∈ R}, the expanding curves tend to be equidistributed in G/Γ, as t → +∞. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Later Shah [Sha09b] studied the case m = 1, and showed that if an analytic curve in R n is not contained in any proper affine subspace, then almost every point on the curve is not DT-improvable. Lei Yang [Yan16a] studied the case m = n, and proved an analogous result for square matrices. These results have been generalized to supergeneric curves in M m×n (R) in the recent preprint [SY16], where an inductive algorithm was introduced to define generic and supergeneric curves.…”
Section: Grassmannians and Dirichlet's Approximation Theorem On Matrimentioning
confidence: 88%
“…Later Shah [Sha09b] studied the case m = 1, and showed that if an analytic curve in R n is not contained in any proper affine subspace, then almost every point on the curve is not DT-improvable. Lei Yang [Yan16a] studied the case m = n, and proved an analogous result for square matrices. These results have been generalized to supergeneric curves in M m×n (R) in the recent preprint [SY16], where an inductive algorithm was introduced to define generic and supergeneric curves.…”
Section: Grassmannians and Dirichlet's Approximation Theorem On Matrimentioning
confidence: 88%
“…We use induction to complete the proof. For the case m = n, the lemma is due to Yang [20]. We provide a proof here.…”
Section: Since This Holds For Every Irreduciblementioning
confidence: 96%
“…Based on the same correspondence, Nimish Shah [18] proved the following stronger result: for m = 1 and general n, if an analytic curve ϕ : I = [a, b] → R n is not contained in a proper affine subspace, then almost every point on the curve is not DT -improvable. For m = n, Lei Yang [20] provided a geometric condition and proved that if an analytic curve ϕ : I = [a, b] → M(n × n, R) satisfies the condition, then almost every point on ϕ is not DT -improvable. The geometric condition given there provides some hint on solving the problem for general (m, n), and will be discussed in detail later.…”
Section: Nimish Shah and Lei Yangmentioning
confidence: 99%
See 2 more Smart Citations